2016
DOI: 10.4103/0974-1208.197661
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between findings of saline infusion sonohysterography and office hysteroscopy in patients with recurrent implantation failure

Abstract: AIM:This study aims to determine the accuracy of saline infusion sonohysterography (SIS) in the diagnosis of intrauterine pathologies in women with recurrent implantation failure (RIF).SETTINGS AND DESIGN:This is a prospective cross-over study which was carried out during the period between December 2013 and July 2014.MATERIALS AND METHODS:The study involved sixty subfertile women with a history of RIF. All cases underwent a transvaginal ultrasonography, SIS and then an office hysteroscopy (1 day after SIS) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…However, in the majority of cases, the cause of RIF remains unknown. 1,6,7 MicroRNAs (miRNAs) are a class of small (approximately 18*22 nucleotide) noncoding RNAs that are critical for the regulation of gene expression. These RNA species mediate posttranscriptional gene expression by binding to the 3 0 -untranslated regions (UTRs), of target mRNAs in a sequence dependent manner, leading to transcript degradation and translational repression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the majority of cases, the cause of RIF remains unknown. 1,6,7 MicroRNAs (miRNAs) are a class of small (approximately 18*22 nucleotide) noncoding RNAs that are critical for the regulation of gene expression. These RNA species mediate posttranscriptional gene expression by binding to the 3 0 -untranslated regions (UTRs), of target mRNAs in a sequence dependent manner, leading to transcript degradation and translational repression.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the majority of cases, the cause of RIF remains unknown. 1,6,7…”
Section: Introductionmentioning
confidence: 99%
“…Separate trials are needed to establish/compare its efficacy with hysteroscopy. Studies comparing SIS with diagnostic hysteroscopy have confirmed that SIS is a reliable alternative (18,19) . We see no reason for which it should not detect residual polyps on scanning after ultrasound guided D &C.…”
Section: Discussionmentioning
confidence: 96%
“…Study comparing Saline Infusion Sonography (SIS) and hysteroscopy for detection of uterine abnormalities concluded that these abnormalities were significantly less likely to be identified with SIS compared to hysteroscopy (P = 0.002). 15 …”
Section: Discussionmentioning
confidence: 99%